Effect of Hydrogen Content in Intrinsic a-Si:H on Performances of Heterojunction Solar Cells. (8th September 2013) - Cho, Yun-Shao; Hsu, Chia-Hsun; Lien, Shui-Yang; Wuu, Dong-Sing; Hsieh, In-Cha
Abstract : Influences of hydrogen content in intrinsic hydrogenated amorphous silicon (i-a-Si:H) on performances of heterojunction (HJ) solar cells are investigated. The simulation result shows that in the range of 0–18% of the i-layer hydrogen content, solar cells with higher i-layer hydrogen content can have higher degree of dangling bond passivation on single crystalline silicon (c-Si) surface. In addition, the experimental result shows that HJ solar cells with a low hydrogen content have a poor a-Si:H/c-Si interface. The deteriorate interface is assumed to be attributed to (i) voids created by insufficiently passivated c-Si surface dangling bonds, (ii) voids formed by SiH2 clusters, and (iii) Si particles caused by gas phase particle formation in silane plasma. The proposed assumption is well supported and explained from the plasma point of view using optical emission spectroscopy.